2014
DOI: 10.15252/embr.201438840
|View full text |Cite
|
Sign up to set email alerts
|

Genetically encoded impairment of neuronal KCC 2 cotransporter function in human idiopathic generalized epilepsy

Abstract: The KCC2 cotransporter establishes the low neuronal Cl À levels required for GABA A and glycine (Gly) receptor-mediated inhibition, and KCC2 deficiency in model organisms results in network hyperexcitability. However, no mutations in KCC2 have been documented in human disease. Here, we report two non-synonymous functional variants in human KCC2, R952H and R1049C, exhibiting clear statistical association with idiopathic generalized epilepsy (IGE). These variants reside in conserved residues in the KCC2 cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
194
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(201 citation statements)
references
References 43 publications
(69 reference statements)
5
194
2
Order By: Relevance
“…Moreover, it is tempting to speculate that inhibitory KCC2 Thr 906 and Thr 1007 phosphorylation might also be pathologically increased in mature neurons, accounting for the documented decrease in KCC2-mediated Cl − extrusion capacity and GABAergic disinhibition in diseases, such as temporal lobe epilepsy (60) and neuropathic pain (61). Mutations in KCC2 associated with human disease, severe idiopathic generalized epilepsy in a large French Canadian patient cohort (43) and febrile seizures in an Australian family (62), are clustered in the C-terminal region and reside in residues close to the Thr 906 and Thr 1007 motifs, which would likely alter KCC2 activity. These subjects will be rich topics of future investigations with potential clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it is tempting to speculate that inhibitory KCC2 Thr 906 and Thr 1007 phosphorylation might also be pathologically increased in mature neurons, accounting for the documented decrease in KCC2-mediated Cl − extrusion capacity and GABAergic disinhibition in diseases, such as temporal lobe epilepsy (60) and neuropathic pain (61). Mutations in KCC2 associated with human disease, severe idiopathic generalized epilepsy in a large French Canadian patient cohort (43) and febrile seizures in an Australian family (62), are clustered in the C-terminal region and reside in residues close to the Thr 906 and Thr 1007 motifs, which would likely alter KCC2 activity. These subjects will be rich topics of future investigations with potential clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, recent genetic studies of patients suffering from idiopathic epilepsy identified mutations within KCC2 (31,32) that decrease S940 phosphorylation and compromise transporter activity. Thus, changes in S940 phosphorylation may contribute to epileptogenesis in humans.…”
Section: Positive Modulation Of Kcc2 Function Upon Inhibition Of Proteinmentioning
confidence: 99%
“…The loss of KCC2 membrane expression underlies neurological and psychiatric disorders including epilepsy (41)(42)(43)(44), stress (45), autism spectrum disorder (46,47), schizophrenia (48), motor spasticity (49), and neuropathic pain (50). Thus, it is essential to elucidate the pathways and mechanisms regulating KCC2 function to develop therapeutic strategies to restore KCC2 expression and synaptic inhibition.…”
Section: Gluk2 Regulates Kcc2 Surface Recyclingmentioning
confidence: 99%